AN ANALYSIS OF FACTORS AFFECTING THE DECISTION TO DEVELOP BANANA WINE PRODUCTS IN KHLONG NIYOM YATRA SUBDISTRICT, BANG BO DISTRICT, SAMUT PRAKAN PROVINCE - Kitbumrungrat, Krieng (Life Sciences and Environment Journal, 2024)
The objectives of the research were: 1) to analyze the components of decision making to choose to develop a banana wine product and 2) to study the factors influencing the decision to choose to develop a banana wine product in Khlong Niyom Yatra Subdistrict, Bang Bo District, Samut Prakan Province. To use the data for analysis and planning to increase sales as a guideline for entrepreneurs' marketing re-strategies. This study is a quantitative research using a survey research method. Descriptive statistics were used to analyze the data including, mean, percentage, and standard deviation, whereas inferential statistics were factor analysis and multiple regression analysis. Results: The research revealed that 4 factors of the marketing mix affecting the decision to develop a banana wine product: 1) product and price factors, 2) marketing promotion and advertising factors, 3) distribution channels and information presenter and 4) personnel and sales service factors. Conclusion: Product and price factors give importance to wine products that transform products to suit community tastes. Distribution channel In terms of marketing promotion and advertising, emphasis is placed on advertising distribution channels, both online and offline. And in terms of personnel and sales services, emphasis is placed on having products with a good reputation and good image.